The crosstalk between mitochondrial dysfunction and fatty acid metabolism in heart failure: mechanisms and therapeutic strategies - Wang, Min; Zhu, Zheqin; He, Xuan; Dai, Sisi; Liu, Rongzhen; Liu, Jianhe (Frontiers in Pharmacology, 2025)
Heart failure is characterized by progressive energetic insufficiency, in which mitochondrial dysfunction and impaired fatty acid oxidation are central features. Normally, the FAO provides most of the cardiac ATP supply, but in HF, this pathway becomes disrupted, leading to the accumulation of lipid intermediates, oxidative stress, and reduced ATP production. Emerging evidence suggests that mitochondrial impairment and FAO disturbances may interact reciprocally, forming a vicious cycle that aggravates energetic failure and structural remodeling. This review summarizes current knowledge on the bidirectional relationship between mitochondrial dysfunction and FAO abnormalities in HF. We integrate findings from experimental models with clinical observations that highlight the translational relevance of this interplay. In addition, we provide an updated overview of therapeutic strategies, including pharmacological modulators such as SGLT2 inhibitors and trimetazidine, as well as traditional Chinese medicine formulas such as Qiliqiangxin and Qishen granules, which have shown preliminary benefits in clinical studies. Although the proposed vicious cycle remains a working hypothesis requiring further validation, understanding this interplay may help identify novel biomarkers, stratify patients by metabolic phenotype, and guide precision therapies for HF.